Counselling Children After Wildfires: A School-Based Approach - Shepard, Blythe; Kulig, Judith; Pujadas Botey, Anna (Canadian Journal of Counselling and Psychotherapy, 2017)
Population growth into wildland-urban interface areas and wildland fires continue to threaten people and property across Canada. This article focuses on the promotion of healing of children affected by wildfires based on results from our mixed methods study outlined in detail previously (Townshend et al., 2015). A brief review of the literature on children and their responses to natural disasters and to wildfires is followed by key findings from our research. School counselling strategies are outlined that can be implemented school wide (i.e., universal programs, support groups, or in the classroom) or through individual or group counselling.